Human trabecular meshwork cell behavior is influenced by collagen scaffold pore architecture and glycosaminoglycan composition. Issue 10 (9th July 2020) - Osmond, Matthew J.; Krebs, Melissa D.; Pantcheva, Mina B.
Abstract: Glaucoma is a degenerative eye disease in which damage to the optic nerve leads to a characteristic loss of vision. The primary risk factor for glaucoma is an increased intraocular pressure that is caused by an imbalance of aqueous humor generation and subsequent drainage through the trabecular meshwork (TM) drainage system. The small size, donor tissue limitations, and high complexity of the TM make it difficult to research the relationship between the TM cells and their immediate environment. Thus, a biomaterial‐based approach may be more appropriate for research manipulations and in vitro drug development platforms. In this work, human TM (hTM) cells were cultured on various collagen scaffolds containing different glycosaminoglycans (GAGs) and different pore architectures to better understand how hTM cells respond to changes in their extracellular environment. Cellular response was measured by quantifying cellular proliferation and expression of an important extracellular matrix protein, fibronectin. The pore architecture of the scaffolds was altered using freeze‐casting technique to make both large and small pores that were aligned or with a non‐aligned random structure. The composition of the scaffolds was altered with the addition of chondroitin sulfate and/or hyaluronic acid. It was found that the hTM cells grown on large pore scaffolds proliferate more than those grown on small pores. There was an increase in the fibronectin expression with the incorporation of GAGs, and its morphology was changed by the underlying pore architecture. This work will help provide an insight into the behavior of hTM cells when introducing changes in their microenvironment. Abstract : To study the behavior of human trabecular meshwork (hTM) cells in response to changes in their microenvironment, scaffolds were made from collagen and different glycosaminoglycans (GAG). Collagen–GAG scaffolds were fabricated using freeze casting techniques to create a variety of pore sizes and alignments to try and replicate the complex extracellular matrix of the trabecular meshwork. These scaffolds were then seeded with hTM cells and their behavior was characterized.